Students’ Problem-Solving Skills Based on Polya’s Stages - Madzkiyah, Azizah Fathanatul; Subanji; Arifin, Slamet (Universitas Tidar, 2024)
Problem-solving is recognized as one of the core aspects of learning mathematics, as it helps students develop essential thinking and reasoning skills. Strengthening problem-solving abilities is also a key goal of mathematics education. The purpose of this study was to analyze students' problem-solving skills based on Polya's theoretical stages. A triangulation approach was applied by combining qualitative methods with data collection through interviews and written tests. The participant consisted of 19 fifth-grade students in an elementary school at Sorong Regency, West Papua, Indonesia. The findings showed that students' problem-solving performance were generally low. Specifically, 15.79% students achieved a high level, 47.73% students were categorized as medium category, and 36.84% students were in the low category. Students with low ability demonstrated difficulties in understanding problems and implement solution steps, while those with medium ability were able to understand problems but often made calculation errors. High-performing students solved problem effectively but tended not to verify their solutions. These results highlight the need for instructional strategies that systematically strengthen students’ problem-solving skills across different ability levels.